Flotation for cell recovery from small volumes of yeast cultures - De Sousa, SR; Laluce, Cecília [UNESP] (Kluwer Academic Publ, 2000)
Flotation or cell recovery in foams (proportion of the total cells in the medium transferred to the foam) and flotation efficiency (proportion of the cells transferred from an initial volume of medium equal to the residual volume after flotation) are functions of time, aeration rate, initial volume of medium, and initial concentration of cells. Cell recovery reached constant values (around 96.4 +/- 6.3%) and flotation efficiency decreased (owing to increases in the liquid content of the foam), with increases in air how rate (above 6-7 ml air s(-1)) and volumes of medium (above 11 ml) added to the column. Increases in concentration of cells in the medium led to increases in the concentration of cells in the foam.
Keywords: cell recovery; column flotation; Saccharomyces cerevisiae; yeast flotation